Posterior reversible encephalopathy syndrome complicated with subarachnoid hemorrhage in an eclamptic pregnant patient: case report - Dan Hu; Jing Xiong; Yunfei Zha; Zhaohui Zhang (BMC Neurology, 2018)
Abstract Background Posterior reversible encephalopathy syndrome (PRES) is a neurotoxic condition which comprises various neurological symptoms. This syndrome could be complicated by intracranial hemorrhage including subarachnoid hemorrhage (SAH). However, SAH is rarely seen in eclamptic patients with PRES. Case presentation A 34-weeks-pregnant woman at the age of 33 was admitted to the obstetrics department because of an episode of generalized tonic-clonic seizure. Before the seizure, the patient had a headache and was found to have an abnormal systolic blood pressure of 160 mmHg. On admission, systolic and diastolic blood pressures were up to 182 and 99 mmHg, respectively. Emergent cesarean section was then performed. On hospital day (HD) 2, cranial non-contrast computed tomography (CT) revealed the existence of SAH. Multiple areas of high signals on T2-weighted and fluid attenuated inversion recovery (FLAIR) sequences were shown by cranial magnetic resonance imaging (MRI) performed 2 days later. CT-angiography studies didn’t reveal intracranial aneurysm. After anti-hypertensive treatment, arterial blood pressure of the patient was gradually tapered to normal values. Eventually, the patient was discharged without any residual symptoms. Conclusions SAH is a rare complication of PRES in eclamptic patients. In patients with PRES, occurrence of SAH is related to increased morbidity and mortality especially when the hemorrhage is diffuse or massive. Our patient had a minor hemorrhage. The good prognosis might also be due to immediate elimination of the risk factor of PRES by emergent delivery.